Extracellular Endothelial Cell-Derived Vesicles: Emerging Role in Cardiac and Vascular Remodeling in Heart Failure - Berezin, Alexander E.; Berezin, Alexander A. (Frontiers in Cardiovascular Medicine, 2020)
Extracellular vesicles play a pivotal role in numerous physiological (immune response, cell-to-cell cooperation, angiogenesis) and pathological (reparation, inflammation, thrombosis / coagulation, atherosclerosis. endothelial dysfunction) processes. Heart failure developing is strongly associated with endothelial dysfunction, microvascular inflammation, alteration in tissue repair, and cardiac and vascular remodeling. It has been postulated that activated endothelial cell-derived vesicles are not just transfer form of several active molecule, such as regulatory peptides, coagulation factors, growth factors, active molecule, hormones) that are embedded onto angiogenesis, tissue reparation, proliferation, and even prevention from ischemia / hypoxia, but they involved in direct myocardial and vascular damage due to regulation of epigenetic responses of the tissue. These responses are under control of several factors, such as micro-RNAs, that are transferred inside extracellular vesicles from mother cells to acceptor cells and are transductor of epigenetic signals. Finally, it is not clear whether different phenotypes of heart failure are result of altered cardiac and vascular reparation due to certain epigenetic responses, which are yielded by co-morbidities, such as diabetes mellitus, and obesity. The aim of the review is to summarize knowledge regarding the role of various types of extracellular endothelial cell-derived vesicles in regulation of cardiac and vascular remodeling in heart failure